Street Quality Monitoring Using IoT - Kalame, Poonam; Shweta Yadav, Saba Kalawant, Manjusha Koli, Prof. M. S. Sonale, (Journal of Electronic Design Engineering, 2020)
Street quality monitoring is a system that aims at warning the driver about the uneven roads and potholes in its path. This system has sensors like the ULTRA sonic sensor, Accelerometer, which will detect the potholes. Surveys will be conducted and data will be stored on the database. This can be manually updated. The user will see the pothole location on Maps which may help him to avoid potholes.